2007
DOI: 10.1097/01.sla.0000253965.95368.52
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Endovascular Repair of Small Abdominal Aortic Aneurysms

Abstract: EVAR can be carried with good perioperative outcome in patients with small AAA; however, intermediate success is hampered by the need for reintervention and continued aortic sac enlargement. At present, widespread treatment of small AAAs by EVAR would appear inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…These rates are very similar to an estimated 74.6% of patients free from any endoleak through to five years and 93.2% free from type I endoleaks in a contemporary Australian cohort. 36 In the ENGAGE study, 89.4% of patients with follow up imaging had declining or stable (61.4% declining, 28.0% stable) sac diameters at five years. This percentage is comparable to early generation results, where 91% of patients had declining or stable (49% declining, 43% stable) sac diameters.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are very similar to an estimated 74.6% of patients free from any endoleak through to five years and 93.2% free from type I endoleaks in a contemporary Australian cohort. 36 In the ENGAGE study, 89.4% of patients with follow up imaging had declining or stable (61.4% declining, 28.0% stable) sac diameters at five years. This percentage is comparable to early generation results, where 91% of patients had declining or stable (49% declining, 43% stable) sac diameters.…”
Section: Discussionmentioning
confidence: 99%
“…A presentation at a recent meeting of the European Society of Vascular Surgery reported that at 3 years, early elective EVAR did not reduce mortality for patients with 40–54mm AAAs 114. Longer term results are awaited 115,116. Recently, it has been suggested that delaying surgery does not alter the anatomical suitability for EVAR 117.…”
Section: 0 Current Diagnosis Of Aaamentioning
confidence: 99%
“…The Australian Safety and Efficacy Register of New Interventional Procedures – Surgical (ASERNIP‐S) is the only health technology assessment group in the world that focuses on surgical procedures. During the 10 years since its inception, this group has developed a strong international profile through the production of more than 60 reports on evidence‐based surgery 1–62 , surgical technologies and audit. In addition ASERNIP‐S has pioneered the introduction of national audits into the surgical community.…”
Section: Overviewmentioning
confidence: 99%